2022
DOI: 10.1177/23996544221100914
|View full text |Cite
|
Sign up to set email alerts
|

Participatory governance in China: ‘Informal public participation’ through neighbourhood mobilisation

Abstract: Public participation is an emergent feature of urban governance in Nanjing, China. Though introduced to address social conflicts around urban redevelopment, the fact is that government-led public participation did not successfully soothe tensions, but resistance instead played a role like ‘public participation’ which influenced the governing processes. This Chinese case thus requires us to rethink the limitations of Western governance theories in explaining this Chinese story. With the purpose to research urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…A critical survey in Nanjing [46] indicates that public participation is the buffer that mediates and 'repairs' the inconsistencies between different levels of governmental agencies. In fact, in the complex urban renewal process, relying solely on government power to fully control environmental remediation and conduct socioeconomic regeneration is extremely difficult; it is necessary to explore and guide social forces effectively.…”
Section: An Emphasis On Participatory Governance In High-density Cent...mentioning
confidence: 99%
“…A critical survey in Nanjing [46] indicates that public participation is the buffer that mediates and 'repairs' the inconsistencies between different levels of governmental agencies. In fact, in the complex urban renewal process, relying solely on government power to fully control environmental remediation and conduct socioeconomic regeneration is extremely difficult; it is necessary to explore and guide social forces effectively.…”
Section: An Emphasis On Participatory Governance In High-density Cent...mentioning
confidence: 99%
“…A study by Cao (2022) has discovered that the theories of public participation in development,participatory governance adopted by the Office of Public Sector Development Commission (OPDC) as their management standard and for execution by Thai government officials presently, are various from the western concept when used in actual technique. The research used qualitative techniques and multiple case studies.…”
Section: Stratford Peer Reviewed Journals and Book Publishing Journal...mentioning
confidence: 99%
“…Scholars in this journal have shown that everyday practices of citizenship fall short of the standards policymakers prescribe (Bartels, 2018;Cao, 2022;Hoekstra, 2018). Participatory governance's understanding of citizenship is often narrow, framing the good citizen by specifying appropriate norms, values, and behavior (De Koning et al, 2015).…”
Section: Introductionmentioning
confidence: 99%